Neighborhood senior daytime community centers in the town planning process in Turkey - Berkoz, Lale (AESOP, 2016)
The growing ratio of elderly individuals within the total population is resulting in an increase in age-related problems. Known as the third age group, the seniors who make up this group face problems that can be classified as physiological, biological, psycho-social, and economic. Oftentimes, loneliness comes to the top of the list of the issues with which these seniors must deal. While developed countries are rapidly instituting new and contemporary measures to establish senior community centers, Turkey, whose average life expectancy has now reached the 70s, has instituted almost no innovations in this area. Turkey does have a system of nursing homes that equate with resident old-age. These are facilities that the aging sometimes enter voluntarily, or are sometimes forced to enter due to certain issues in their lives. It is a well-accepted fact that the residents of these facilities live the remainder of their lives isolated from the greater community. It is thus that the wide experience and knowledge that have been amassed by the elderly are simply tossed aside, constituting a significant loss for society. This isolation of the aging also means that these individuals both feel remote from society and suffer a loss in quality of life.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south